Silleras-Fernández, Nuria. The Politics of Emotion. Love, Grief, and Madness in Medieval and Early Modern Iberia. Cornell University Press, Ithaca & Londres, 2024, 372 pp. ISBN: 978-1-5017-7386-0: no - Martínez Alcorlo, Ruth (Revista de Filología Románica, 2025)
no